Individual luteolysis post GnRH-agonist-trigger in GnRH-antagonist protocols. (3rd April 2017) - Lawrenz, B.; Ruiz, F.; Engelmann, N.; Fatemi, H. M.
Abstract: Over the past few years, the use of Gonadotropin-releasing-hormone (GnRH)-agonist for final oocyte maturation in GnRH-antagonist-protocols in stimulated IVF/ICSI cycles has gained worldwide acceptance, as this approach reduces significantly the risk for development of ovarian hyperstimulation syndrome (OHSS). Final oocyte maturation with GnRH-agonist leads to sever luteolysis, which cannot be counterbalanced using standard luteal phase support with purely progesterone (P4) application and therefore administration of hCG or high doses of P4 is considered to be essential to prevent/counteract luteolysis. However, lately publications indicate, that luteolysis is not always complete after GnRH-agonist for trigger. This case-series evaluates the degree of luteolysis in high-responder-patients, who received GnRH-agonist for final oocyte maturation. Assessment of estradiol (E2)- and P4-levels 48 h after oocyte-pick-up (OPU) procedure demonstrate clearly, that luteolysis after GnRH-agonist trigger is individual-specific, even in high-responder patients with the same number of oocytes. Hence, individualization of luteal phase support with the focus on avoiding unnecessary administration of hCG, bearing the risk for development of OHSS, a new concept of luteal coasting needs to be developed, based on severity of luteolysis following luteal coasting.